Analysis of BE and rtPS QoS in WiFi network - Mohd Sultan, Juwita; Markarian, Garik; Benachour, Philip (Yerevan: Republic of Armenia national academy of sciences, 2018)
Quality of Service (QoS) in networking is defined as the assurance or as a guarantee factor that the information is perfectly delivered in a communication link.As one of the promising novel in the next communication architecture is to have a coherence quality of service in a wireless hybrid network.However,these heterogeneous networks have various levels of QoS classes. WiFi, for example, has two classes of QoS, five classes in WiMAX while nine classes are in LTE. Since each system has a particular level of QoS classes, the motivation to have a persistent communication is a challenging task. In this paper, we investigate on details of the QoS in WiFi network first before proceed to the hybrid network. The QoS involve are real time polling service (rtPS) and Best Effort (BE).Thus ,in this paper, we propose QoS table for WiFi network with the consideration of the user’s application. We will evaluate the traffic outputs based on the application assigned to the end users. The propose structure will be analyzed using Opnet modeler simulation tool with the essential parameters which are throughput, delay and packet loss.The motive of this research is to have an optimize throughput,minimum amount of delay as well as zero tolerance on the packet loss.Therefore,a hybrid communication system benefited to all,especially for future user applications will be the significant from this research.